HUBUNGAN SUMBER INFORMASI , KETERSEDIAAN FASILITAS, PERAN BIDAN DAN SIKAP TERHADAP MOTIVASI IBU DALAM PEMANFAATAN POSYANDU DI DESA MARGATANI WILAYAH KERJA KRAMATWAT - Sri Susanti; Lina Marliana (Poltekkes 'Aisyiyah Banten, 2021)
Optimal growth and development has a goal in order to be able to shape children into human beings who have quality by not only experiencing growth in a physical aspect but also having the ability to have utility and good results for themselves, their families, society, the nation and also the whole. mankind. Therefore, childhood needs to get attention (1).The general objective is to find out the relationship between information sources, the availability of facilities, and attitudes towards the activeness of mothers in monitoring the growth and development of children under five at Posyandu, Margatani Village, in the working area of ​​the Kramatwatu Community Health Center. The research method was survey and cross sectional approach. The population of this study were mothers who had children under five in Margatani village, amounting to 45 children. The tool used for data collection was a questionnaire.Research Results It was found that 22% of mothers who were not active in monitoring the growth and development of their toddlers at the Margatani Village Posyandu It was found that mothers had a poor attitude towards monitoring the development of children under five by 28%, There was no relationship between sources of information and the activeness of mothers in monitoring the development of children under five at Posyandu at Margatani Village and there was a relationship between the availability of facilities and attitudes with the activeness of mothers in monitoring the growth and development of children under five in Posyandu, Margatani Village, Kramatwatu Community Health Center working area. Suggestions for the need to increase health promotion efforts, especially regarding the use of posyandu for monitoring the development of children under five with easy-to-understand media in order to increase good understanding to respondents